On the American style futures contracts - Tsvetelin Zaevski (Croatian Operational Research Review)
There is a large number of sources devoted to the American style options. On the other hand, the American futures contracts are understudied in the scientific literature. This motivated us to examine these instruments in comparison to the relevant options. Their optimal boundaries are obtained and a finite difference scheme is applied to the pricing problem. We consider separately the long and short positions.